Prevalence and Predictors of Anxiety and Depression among Female Medical Students in King Abdulaziz University Jeddah Saudi Arabia (Tehran University of Medical Sciences, 2013)
Background: Medical education & medical profession are among the most challenging and most stressful ones. Anxiety and depression represents an escalating public health problem among medical students. The objective of the study was to determine the prevalence & predictors of anxiety and depression among female medical students in King Abdulaziz University, Jeddah, Saudi Arabia.Methods: A cross- sectional study was carried out during 2010-2011. A stratified random sample method was used to select 450 medical students. A confidential, anonymous & self administered questionnaire included Standardized Hospital Anxiety & Depression Scale was used.Results: The mean scores for anxiety and depression were 9.32 ± 3.77 & 6.59 ± 3.62, respectively. There is a positive correlation between anxiety & depression scores (r= 0.52, P< 0.001). Prevalence of morbid anxiety and depression were 34.9% and 14.7%, respectively. Logistic regression analysis revealed that the first predictor of morbid anxiety was depression (adjusted Odds Ratio (aOR) = 3.28; 95% Confidence Interval (CI): 1.85-5.82, P < 0.001). Students complained from condensed academic course, had academic and emotional failures during the 6 months preceded the study were about 2 times more prone to anxiety. Predictors of depression were having anxiety, nationality (being non-Saudi) & having emotional failure.Conclusion: Medical students encountered high rates of anxiety & depression compared to others. Academic problems and major life events were the main predictors. Enhancing faculty preventive & curative mental health services is recommended. Initiation of stress management courses & enhancing academic advising services are required since the start of medical education.